The Protective Effect of Basic Fibroblast Growth Factor on Diabetic Nephropathy Through Remodeling Metabolic Phenotype and Suppressing Oxidative Stress in Mice - Wei, Tingting; Shu, Qi; Ning, Jie; Wang, Shuaijie; Li, Chen; Zhao, Liangcai; Zheng, Hong; Gao, Hongchang (Frontiers in Pharmacology, 2020)
Diabetic nephropathy is a common complication in diabetes, but still lack of effective therapeutic strategies. This study aimed to investigate the therapeutic effect of basic fibroblast growth factor (bFGF) in db/db mice with diabetic nephropathy and explore its possible metabolic mechanisms using an NMR-based metabolomic approach. We found that bFGF treatment significantly alleviate urinary albumin to creatinine ratio and renal fibrosis in db/db mice, suggesting a potential renal protective effect. Metabolomics results reveal that bFGF remodeled metabolic phenotypes of the kidney and urine in db/db mice, mainly involving energy metabolism, methylamine metabolism, osmoregulation and oxidative stress. Furthermore, the results show that bFGF-induced reductions of oxidative stress and apoptosis in db/db mice might be mediated by NOX‐ROS‐Nrf2 signaling. Therefore, our study suggests that the protective effect of bFGF on diabetic nephropathy could be mediated by remodeling metabolic phenotype and suppressing oxidative stress.